Pengaruh Pengembangan Model Suami Siaga terhadap Dukungan Suami pada Pelaksanaan Inisiasi Menyusu Dini - Rosmadewi, Rosmadewi; Aliyanto, Warjidin (Poltekkes Kemenkes Tanjung Karang, 2022)
Breastfeeding is one of the first steps for a human being to get a healthy and prosperous life. UNICEF states that IMD is one of 10 steps towards successful breastfeeding that will have a positive impact on the health of mothers and babies. Babies who are allowed to breastfeed early are eight times more successful in exclusive breastfeeding and breastfeeding for a long time until the age of 2 years. This study aims to determine the effect of the development of the standby husband model on the husband's support in preparation for the implementation of Early Breastfeeding Initiation. This type of research is a quantitative (analytic) research method using a quasi-experimental design with a post-test-only control group design. The research subjects were husbands of multigravida mothers with a gestational age of 32 weeks with a total of 94 people. Collecting data using primary data. Univariate data analysis using percentages and bivariate analysis using chi-square. The results showed that there was an effect of developing the standby husband model by giving a pocketbook to the husband's support in preparation for the implementation of Early Breastfeeding Initiation (IMD) with a p-value of 0.01, Suggestions are addressed to midwives who provide services to pregnant women and maternity mothers to include husbands in preparation for the implementation of Early Breastfeeding Initiation by providing information about the need for husband's support in preparation for the implementation of IMD through the provision of pocketbooks.Â